Grub mtha' śel gyi me loṅ - Chos-kyi-nyi-ma, Thuvu-bkwan III. (Bod kyi gtsug lag gces btus pod phreṅ, 2007)
Study on development of different religious sects of Tibetan Buddhism and their interpretation of Buddhist philosophy